The Counter-Narrative of and about the Pregnant Black Woman: opposition to ahistoricism in the United States - Ferreira, Telma Sueli Farias; Xavier, Manassés Morais (The ESPecialist, 2025)
The historical narratives of ingroups formed by white subjects tell us only one version of history, hiding all the experiences lived by black people, both in the past and in the present day. Furthermore, in addition to the attempt to silence our voice, the concrete-dialogical statement of white people seeks to erase the link between the origins and practice of colonial racism and the racist crimes of today. Given this reality, we intend to investigate the dialogical relations between the counter-narratives of former slaves and the statements of black pregnant women in the contemporary world, regarding the racist reality of obstetric violence that they experience in the United States, thus indicating the potential of this discursive genre as an element that is adverse to the ahistoricism of hegemonic whiteness. Methodologically, we are guided by the Dialogical Theory of Language, which offers us concepts about dialogism, sign and active responsive attitude as categories of analysis. For the investigation, the corpus of this research comprises the counternarratives uttered by pregnant black women: of the past, formerly enslaved (based on the book “Nascidos na Escravidão: depoimentos norte-americanos”); and free women of today (based on videos from ABC News and Indiscutible with Dr. Rashad Richey Youtube channels), who reveal different types of violence against black female bodies during childbirth. The theoretical discussion is based on Tate (1997), Delgado (1998), Fiorin (2008), Bakhtin (2011 [1979]), Volóchinov (2019 [1926]; 2021 [1929]), Lister et al. (2019), Parron (2020), Arnold (2023), Odems et al., (2024), among others. The results point to the relationship between the mistreatment of black women during childbirth in the current context and the violence and neglect perpetrated against enslaved women, thus reaffirming that dialogical-ideological relations are woven in the discursive arena of clashes and disagreements between black and white Americans.